2022
DOI: 10.3846/btp.2022.13929
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Marketing Activities and Promotions on the Consumers Buying Behavior

Abstract: The core purpose of this study is to determine the impact of electronics marketing (word of mouth), perceived value, and social networking on customer buying behaviour through customer trust in the context of cosmetic industry of Jordan. To accomplish the main research objective, the study has followed SEM technique for analysing collected data. For data collection, the use of survey questionnaire has been made, in which data was collected from total 223 respondents. The results of this study confirm the signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The results indicated that AVE was superior to MSV among all research constructs, as well as that the square root of AVE exceeded all correlation coefficients. According to these results, the measurement model was considered to have discriminant validity (Alhalalmeh et al, 2022;Franke&Sarstedt, 2019). Furthermore, the composite reliability was verified using McDonald's Omega coefficients that ranged within the domain (0.795-0.844).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…The results indicated that AVE was superior to MSV among all research constructs, as well as that the square root of AVE exceeded all correlation coefficients. According to these results, the measurement model was considered to have discriminant validity (Alhalalmeh et al, 2022;Franke&Sarstedt, 2019). Furthermore, the composite reliability was verified using McDonald's Omega coefficients that ranged within the domain (0.795-0.844).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…Loyalty can be broadly defined as a positive feeling that a customer may exhibit toward a brand, service, or activity. It's more of a trait in the customer than something inherent in the brand (Alhalalmeh et al, 2022;Al-Hawary, 2013). Loyalty is defined by Jamil et al (2019) as a personal behavior that expresses the inclination towards a particular brand over another and the customer's intent to buy that brand again in the future.…”
Section: Brand Loyaltymentioning
confidence: 99%
“…The aspect of green marketing has been recently studied in various studies. Nowadays, it is known as a major concept in organizations and various organizations are accepting and implementing green marketing and its relevant programs (Papadas, Avlonitis, & Carrigan, 2017;Alhalalmeh et al, 2022;Rosenbaum & Wong, 2015). The presence of green programs and initiatives has significantly helped in creating green products in different organizations that include automobiles, food, tourism, construction, and energy (Ali, 2020;Tariq et al, 2022;Al-Abbadi et al, 2022;Mohammad et al, 2022;Naidoo & Gasparatos, 2018;Pan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%